Substrate Composition and the Effect of ε-Aminocaproic Acid on Tissue Plasminogen Activator and Urokinase-induced Fibrinolysis - Thorsen, Sixtus; Astrup, Tage (Thrombosis and Haemostasis, 1974)
The influence of variations in substrate composition on the biphasic pattern of inhibition by e-aminocaproic acid (EACA) of urokinase-induced fibrinolysis, first observed on bovine plasminogen-rich fibrin, was studied using a fibrin clot lysis time assay. Different species of fibrinogen and plasminogen or plasmin were used. Preparations of different degrees of purification were compared at varying concentrations. The behavior of urokinase was compared with that of a porcine tissue plasminogen activator. Variations in the conditions of the assay greatly influenced the results. The concentration of fibrinogen had a particularly marked influence. At increased fibrinogen concentrations the biphasic response of urokinase was enhanced and a weak biphasic effect was also produced by the tissue activator which usually yields a uniformly increasing inhibition curve. The phase of fibrinolysis enhancement produced by urokinase with genuine plasminogen substrates occurs at substrate concentrations and EACA levels present in patients treated with EACA. The observed variations may explain discordant findings reported by various investigators.